2017
DOI: 10.1038/s41598-017-12912-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship Studies of β-Lactam-azide Analogues as Orally Active Antitumor Agents Targeting the Tubulin Colchicine Site

Abstract: We have synthesized a series of new β-lactam-azide derivatives as orally active anti-tumor agents by targeting tubulin colchicine binding site and examined their structure activity relationship (SAR). Among them, compound 28 exhibited the most potent antiproliferative activity against MGC-803 cells with an IC50 value of 0.106 μM by induction of G2/M arrest and apoptosis and inhibition of the epithelial to mesenchymal transition. 28 acted as a novel inhibitor of tubulin polymerization by its binding to the colc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Previous studies have investigated different compounds containing the 3,4,5trimethoxyphenyl ring in order to understand its contribution to the biological activity [21]. For example, in a study performed by Dong-Jun et al, the authors showed that 3,4,5trimethoxyphenyl moiety at the N-1 position of the β-lactam-azide derivatives was crucial for the antiproliferative activity against MGC-803, MCF-7, and A549 cancer cell lines [22]. Furthermore, anticancer compounds such as colchicine, steganacin, phenstatin, podophyllotoxin, combretastatin, and other synthetic analogues of these compounds share a 3,4,5-trimethoxyphenyl moiety as a common structural feature [23].…”
Section: Structure-activity Relationship (Sar)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated different compounds containing the 3,4,5trimethoxyphenyl ring in order to understand its contribution to the biological activity [21]. For example, in a study performed by Dong-Jun et al, the authors showed that 3,4,5trimethoxyphenyl moiety at the N-1 position of the β-lactam-azide derivatives was crucial for the antiproliferative activity against MGC-803, MCF-7, and A549 cancer cell lines [22]. Furthermore, anticancer compounds such as colchicine, steganacin, phenstatin, podophyllotoxin, combretastatin, and other synthetic analogues of these compounds share a 3,4,5-trimethoxyphenyl moiety as a common structural feature [23].…”
Section: Structure-activity Relationship (Sar)mentioning
confidence: 99%
“…For this study, a series of 32 analogues of 1 (Scheme 1) were synthesized, preserving the (E)-3-(3,4,5-trimethoxyphenyl)-acryloyl moiety on cinnamic esters and amides and changing this moiety on benzoic esters by removing the ethylene group between carbons 2 and 3. Side-chain modi cations were also evaluated changing the radical R to methyl (5), ethyl (6), propyl (7), iPr (8), butyl (9), pentyl (10), decyl (11), 2-methoxyethyl (12), 4-methoxybenzyl (13), phenylethyl (14), 4-methylphenylethyl (15), carvacryl (16), CHPh 2 (17), furfuryl (18), eugenyl (19), (−)-bornyl (20) and piperonyl (21) on cinnamic esters, and butyl (22), N,N-diethyl (23), octyl (24), cyclohexyl (25) benzyl (26), pyrrolidyl (27), 4-methylbenzyl (28), 4-methoxybenzyl (29), 4-uorobenzyl (30), 4-chlorobenzyl (31), 4-bromobenzyl (32) 2,4-dimethoxybenzyl (33), and 3,4-dimethoxybenzyl (34) on amides. e benzoic esters synthetized were 2methoxyethyl-3,4,5-trimethoxybenzoate (35) and benzyl 3,4,5-trimethoxybenzoate (36) [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of extensive use, many bacteria have developed resistance to -lactam antibiotics. Additionally, the antiproliferative activity of compounds containing the -lactam (azetidin-2-one) ring structure has been investigated (Zhou et al 2018;Galletti et al 2014;Geesala et al, 2016;Arya et al, 2014;Fu et al, 2017). We have previously demonstrated the effectiveness of 1,4-diarylazetidin-2-ones in breast-cancer cell lines as tubulin-targeting antimitotic agents and selective estrogen-receptor modulators (SERMs;O'Boyle et al, 2014).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Small molecule tubulin polymerization inhibitors have been reported in which the cis double bond of CA-4 has been replaced by various heterocycles such as furan [25], indole[26,27], imidazole [28], isoxazole [29], triazole [30], tetrazole [31], benzoxepine [32], pyrazole [33], pyridine [34], benzimidazole [35] and related heterocycles [36]. While β-lactam antibiotics have occupied a central role in the treatment of pathogenic bacteria, the antiproliferative activity of compounds containing the β-lactam (azetidin-2-one) ring has also been investigated [37,38,39,40,41,42]. The synthesis and antitumour activity of a number of chiral β-lactam bridged CA-4 analogues have been reported [37,38].…”
Section: Introductionmentioning
confidence: 99%